Growth study of coi fish larvae fed chydoridae - Henneke Pangkey; Sartje Lantu; Revol D. Monijung (Sam Ratulangi University, 2019)
First culture media for chydoridae used horse manure dried in the sun with a composition of 10 grams and 50 grams of soil dissolved in 1 L of water for 5 days, then filtered and diluted three times. Laboratory-scale cultures were carried out in a 500 ml volume jar containing horse manure culture media; then in the process fed with bread yeast and rice bran (0.05 gr yeast and rice bran/500 ml) every 3 days. Mass culture uses 12 jar containers with a volume of 3 L.The administration of chydoridae to two-day old koi fish larvae was carried out with the following treatments: treatment A, which was ornamental fish fed with boiled egg yolk in ad libitum; treatment B is ornamental fish fed with 5 individual chydoridae/ml and treatment C, which is not given any food with three replications. The design of the response in this study was to see the survival rate of ornamental fish larvae (%).The results of measurements of water quality during the study showed that the temperature during the study was 27°C, while the pH was 7. From the statistical analysis it was found that administration of chydoridae had a significant effect on the survival of two-day-old koi fish larvae which were kept for 14 days.Keywords: chydoridae, life feed, ornamental fish larvae, growthABSTRAKMedia kultur awal chydoridae menggunakan kotoran kuda yang dikeringkan di bawah sinar matahari dengan komposisi 10 gram kotoran kuda serta 50 gram tanah yang dilarutkan dalam 1 L air selama 5 hari, kemudian dilakukan penyaringan dan diencerkan sebanyak tiga kali. Kultur skala laboratorium dilakukan dalam wadah toples dengan volume 500 ml berisi media kultur kotoran kuda; selanjutnya dalam proses kultur chydoridae diberi makan ragi roti dan dedak (0,05 gr ragi dan dedak /500 ml) setiap 3 hari sekali. Kultur massal menggunakan wadah toples sebanyak 12 buah dengan volume 3 L dengan mengikuti metode pada kultur skala laboratorium.Pemberian chydoridae kepada larva ikan koi yang berumur dua hari dilakukan dengan beberapa perlakuan sebagai berikut : perlakuan A yaitu ikan hias diberi makan kuning telur rebus secara ad libitum; perlakuan B yaitu ikan hias diberi makan chydoridae 5 individu/ml dan perlakuan C yaitu ikan hias tidak diberi makan apapun dengan tiga ulangan. Rancangan respons dalam penelitian ini adalah melihat laju kelangsungan hidup larva ikan hias (%).Hasil pengukuran kualitas air selama penelitian menunjukkan, suhu selama penelitian adalah 27 °C, sedangkan pH adalah 7. Dari hasil analisis statistik diperoleh bahwa pemberian chydoridae sangat memberi pengaruh nyata kepada kelangsungan hidup larva ikan koi berumur dua hari yang dipelihara selama 14 hari.Kata kunci: chydoridae, pakan alami, larva ikan hias, pertumbuhan